EFEKTIVITAS PELAKSANAAN PEMBERIAN MAKANAN TAMBAHAN (PMT) PEMULIHAN BAGI ANAK USIA BAWAH LIMA TAHUN (BALITA) DENGAN GIZI KURANG DI DESA WATUBONANG KECAMATAN BADEGAN KABUPATEN PONOROGO - Amala, Hafiza Zulfa; Ruhana, Amalia (Jurnal Gizi dan Kesehatan Nusantara, 2023)
Under nutrition on toddlers are a condition where based on the results of measuring body weight for length/height, toddlers have measurement results between minus 3 (-3SD) to less than minus two standard deviations (<-2SD). One of the efforts made by the government to overcome the problem of malnutrition in Indonesia by providing Supplemental Food (PMT) both PMT Recovery and Counseling. The purpose of this study was to knowing changes in body weight, nutritional status, knowing consumption compliance and family support and health workers before and after given PMT. Methods of this study was quantitative research through analytic observational studies with a case study design. This study was conducted in Watubonang Village, Badegan District, Ponorogo Regency and was carried out from August to October 2022. The sample in this study was 33 toddlers that is the entire population of malnutrition toddlers who met the inclusion criteria. The results of the study showed the effectiveness of PMT implementation which showed a difference in body weight before and after given PMT p=0.000 and an increase in the number of toddlers with normal nutritional status by 75.8%. 66% of respondents were adhere in consuming PMT, and 52.5% of respondents received support in the good category from their families. Also 57.6% of respondents received support from health workers in the good category. The conclusion is that there is effectiveness in the implementation of PMT for recovery under nutrition on toddlers in the Watubonang Village, Ponorogo Regency